Progressions in cathodic catalysts for oxygen reduction and hydrogen evolution in bioelectrochemical systems: Molybdenum as the next-generation catalyst - Mishra, Puranjan; Sudarsanam, Putla; Mahapatra, Durga Madhab; Elmekawy, Ahamad; Pant, Deepak; Singh, Lakhveer (Catalysis Reviews- Science and Engineering, 2023)
Oxygen reduction reactions (ORRs) are unanimously a key factor of system performances in bioelectrochemical systems (BESs), low-temperature fuel cells, and generally in several electrochemical platforms. Platinum (Pt)-based catalyst is the finest electrocatalyst for ORR in BESs; however, it is constrained by its low abundance, high price, and poor catalytic durability in an electrochemical setup for cathodic reaction kinetics. In recent years, significant efforts in trimming the metal-based catalyst up to nanoscale to cater high performance of ORR have been explored. Still, there are many opportunities to improve catalyst performance at cathode through proper selection of an efficient low-cost metal-based ORR catalyst. Molybdenum (Mo) with its multi-dimensional form as 2D and 3D layers and synergistic combination with other non-metals offers prospects of extraordinary performance as low-cost metal-based ORR catalyst over the Pt in delivering enhanced ORR potential. The present review throws light on current requirements of a sturdier catalyst material and thus provides a comprehensive review on the continuing efforts in exploring the possibility of Mo as a low-cost metal-based ORR catalyst. This literature analysis would enlighten the significance of ORR in BESs, followed by the electrochemistry of Mo-based cathodic catalyst, its underlying mechanism and performance limiting factors in the operation of ORR. Moreover, the extensive and systematic acumen in the context of Mo-based catalytic formulations for increased ORR potentials including nano-composite Mo-cathode catalyst; development of Mo-catalyst with varied configurations; carbon-supported Mo-catalyst; morphological changes; surface area modifications; and Mo-coupling with other transition metal and its derivatives were discussed in great detail to provide prospective application of Mo-based catalyst. Lastly, numerous opportunities and projections for future research in fabrication, juxtaposition, and implementation of Mo-based cathodic catalysts and consequent recommendations were discussed as conclusive remarks for bringing out the state-of-the-art review on this subject.
Keywords: Bioelectrochemical system; catalytic formulations; H-2-evolution reaction; Mo-based cathodic catalyst; multifunctional catalysts; oxygen reduction reaction